Mutation Update for UBE3A Variants in Angelman Syndrome. Issue 12 (December 2014) - Sadikovic, Bekim; Fernandes, Priscilla; Zhang, Victor Wei; Ward, Patricia A.; Miloslavskaya, Irene; Rhead, William; Rosenbaum, Richard; Gin, Robert; Roa, Benjamin; Fang, Ping
ABSTRACT Angelman syndrome is a neurodevelopmental disorder caused by a deficiency of the imprinted and maternally expressed UBE3A gene. Although de novo genetic and epigenetic imprinting defects of UBE3A genomic locus account for majority of Angelman diagnoses, approximately 10% of individuals affected with Angelman syndrome are a result of UBE3A loss‐of‐function mutations occurring on the expressed maternal chromosome. The variants described in this manuscript represent the analysis of 2, 515 patients referred for UBE3A gene sequencing at our institution, along with a comprehensive review of the UBE3A mutation literature. Of these, 267 (10.62%) patients had a report issued for detection of a UBE3A gene nucleotide variant, which in many cases involved family studies resulting in reclassification of variants of unknown clinical significance (VUS). Overall, 111 (4.41%) probands had a nucleotide change classified as pathogenic or strongly favored to be pathogenic, 29 (1.15%) had a VUS, and 126 (5.0%) had a nucleotide change classified as benign or strongly favored to be benign. All variants and their clinical interpretations are submitted to NCBI ClinVar, a freely accessible human variation and phenotype database.